2022
DOI: 10.1093/tas/txac016
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of polyclonal antibody preparations from avian origin on nutrient digestibility and performance of backgrounding beef cattle

Abstract: This study evaluated the effects of feeding an avian-derived polyclonal antibody preparation (PAP; CAMAS, Inc.) against Streptococcus bovis, Fusobacterium necrophorum, and lipopolysaccharides (40, 35, and 25% of the preparation, respectively) on growth performance (Exp. 1) and apparent total tract digestibility of nutrients (Exp. 2) of beef cattle consuming a backgrounding diet. In Exp. 1, Angus crossbred heifers (n = 70; 360 ± 24 kg of initial body weight; BW) and steers (n = 20; 386 ± 24 kg of BW) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that feeding PAP increased DMI by 8.1% in backgrounding beef cattle ( Silva et al, 2022 ) or had no impact on DMI of beef steers ( DiLorenzo et al, 2008 ; Blanch et al, 2009 ). In the current study, DMI was not affected by the inclusion of PAP throughout the study; however, DMI gradually reduced with corn inclusion.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have reported that feeding PAP increased DMI by 8.1% in backgrounding beef cattle ( Silva et al, 2022 ) or had no impact on DMI of beef steers ( DiLorenzo et al, 2008 ; Blanch et al, 2009 ). In the current study, DMI was not affected by the inclusion of PAP throughout the study; however, DMI gradually reduced with corn inclusion.…”
Section: Discussionmentioning
confidence: 92%
“…It is suggested that IgY can agglutinate bacteria, inhibit bacterial adhesion, suppress the bacteria virulence factors, neutralize toxins, and inactivate enzymes ( Xu et al, 2011 ). Previous research demonstrated that a PAP blend against S. bovis , F. necrophorum , and LPS, presented a positive effect on apparent total tract digestibility of the neutral detergent fiber in beef cattle consuming a nonforage backgrounding diet ( Silva et al, 2022 ). Such effects could be explained by the potential of PAP to increase ruminal pH as observed by DiLorenzo et al (2006) , Blanch et al (2009) , and Marino et al (2011) when using PAP against S. bovis and F. necrophorum into high-grain diets of beef steers, beef heifers, and Holstein cows, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of polyclonal antibodies has been effective against bovine rotavirus and coronavirus, as well as Salmonella, Staphylococcus , and Pseudomonas (Mine and Kovacs-Nolan, 2002 ). Polyclonal antibodies generated toward Streptococcus bovis and Fusobacterium necrophorum dosed in the rumen decreased the abundance of targeted bacteria as measured by most probable number (MPN) viable cell counts (DiLorenzo et al, 2006 , 2008 ) but had varying effects on dry matter intake, volatile fatty acid concentrations, and rumen pH (Marino et al, 2011 ; Silva et al, 2022a , b ). Avian antibodies have also been investigated to reduce methane produced by ruminal archaea (Cook et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%